Orthostatic Test - ein Tool zur Optimierung der Belastungssteuerung - Hottenrottt, L. (Herzfrequenzvariabilität: Methoden und Anwendungen in der Sportwissenschaft, Arbeits- und Intensivmedizin sowie Kardiologie. 7. Internationales HRV-Symposium am 4. März 2017 in Halle (Saale), 2018)
The key to success in high performance sports is the optimization in planning and timing of training stimuli and rest periods to avoid overloading and overtraining. It is the aim of this article to pass on comprehensive experience with the Orthostatic Test (OT) and the resulting changes for individual training and trainings control to interested scientists, coaches and athletes. The OT is a special position-change test with heart rate monitoring in RR mode for 3 minutes while lying and 3 minutes while standing. The OT was performed with the heart rate monitor V800 (Polar, Finland). Test evaluations are carried out with the "PolarFlow" program. Vagal heart rate variability parameters RMSSD are analyzed during supine and standing position, heart rate (HR) during supine and standing position, and HF peak immediately after active standing up. Monitored tests and training protocols of a female elite long-distance runner from August 2014 to February 2017, selected training sessions from general preparation, training camps and competition season were analyzed.